Political and institutional drivers of social security policy in South Africa - Marianne S. Ulriksen; Sophie Plagerson (United Nations Research Institute for Social Development (UNRISD), 2017)
This paper provides an analysis of political and institutional drivers that shape social policy in South Africa with a specific focus on social security. As elsewhere in the Global South, South Africa has a quite extensive social assistance framework, whereas social insurance is limited and inadequate. This is contrary to the experiences of the Global North, where social insurance has been the primary social security mechanism with social assistance playing a more marginal role. In order to explore the contrasting developments within social security policy, we focus our analysis on two case studies with varying policy outcomes: 1) the social cash transfer system, which is well established; and 2) the National Health Insurance (NHI) scheme, a recent policy, which has suffered several delays. Building on the power resource and historical institutionalism approaches, we explore how different actors seek to assert their policy preferences, and how current institutional arrangements shape actors' interests and their ability to influence policy reforms. The two cases reveal interesting differences that can explain the success of social cash transfer expansion and the sluggish progress (to date) to introduce national health insurance. While the latter has strong vested interests against reform, even though there is consensus on the need for a national health insurance scheme, the former has had no strong opponents and subsequent incremental expansions have benefited from well-established institutional arrangements, positive research evidence and civil society advocacy and litigation. Moreover, the introduction of a health insurance scheme is relatively more complex (politically, institutionally and technically), compared to expanding an already existing social cash transfer programme. In our analysis, we also explore the different ideational narratives related to the two types of policies. Social cash transfers have legitimacy as a policy addressing the needs of the most vulnerable, which are defined to be the elderly, young and people living with disabilities, but not able-bodied adults. In the case of health insurance, ideological narratives are pitted against each other: the concept of health as a common good against health as a commodity, and market-oriented strategies for delivery against state-centric approaches.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives from and for the Global South
Keywords: 330